STUDI TAKHRIJ HADIS MENGGUNAKAN METODE TASHIH, MUQORONAH, TAHLIL, TARJIH, DAN TAKHKIM (TMT3) TERHADAP HADIS TENTANG PENYEBARAN COVID-19 - Reza Pahlevi Dalimunthe; Ahmad Rizki; Alria Nunggal; Amanah Amnun Zulfa; Asep Hendra Saiddudin; Siti Nurkholishoh (Jurnal Studi Hadis Nusantara, 2021)
The Coronavirus pandemic or known as the COVID-19 pandemic is one of the events that emerged at the end of 2019. This virus is caused by a new type of Coronavirus named SARS CoV-2. Sars-Cov2 which is the cause of COVID-19 is a virus that can enter and attack the human respiratory system. The disease caused by this (SARS CoV-2) is spreading and spreading rapidly. Referring to the hadith of the Prophet SAW, it is explained that the Prophet also provided signs to overcome the dangers of disease so that it is not quickly transmitted. This is important to follow up as well as as a preventive measure for the spread of COVID-19. This research examines the authenticity and origin of the hadiths regarding the Prophet’s advice in preventing this outbreak using the TMT3 takhrij method, a new method of hadith-sanad-matan criticism, which is supported by digital searches for word indexes in the Jaami ‘al-Kutub al-Tis’ah application, for search for various hadiths using keywords in the application. Also reviewing what is COVID-19 and how the Prophet prevented the spread of disease outbreaks that had occurred in ancient times through qualitative research methods with data collection techniques through library research. Where the results of this study, namely that the quality of the hadith regarding the Prophet’s recommendation as a form of prevention of the spread of the plague is authentic, of course, seen from the narrator’s tsiqqah quality So that this hadith becomes one of the references to the authentic hadith that must be practiced in the face of the current COVID-19 outbreak.